TRANSFORMATION OF IDENTITY AND CULTURAL GLOBALIZATION - Zafer DURDU (Fırat University, 2021)
Identity, for social scientists, is a concept considered together with the phenomenon of modernity and still continuing its dynamism in today’s world. With in